Developing and streamlining clinical trial services to support pediatric drug development across 21 countries in Europe: insights from the conect4children (c4c) network - Attar, Sabah; Figueiras, Francisca P.; Peacock, Carla; Wohlfahrt, Hazel; Hüsken, Birgitta C. P.; Andrews, Susan; Lepola, Pirkko; Patton, Margaret; Hankard, Regis; Halil, Eren; Soares, Fernando Pontes; Tan, Lionel K.; et al. (Frontiers in Medicine, 2025)
The efficiency, quality, and scalability of clinical trial support services are essential for the success of multinational clinical trials particularly trials that recruit babies, children, and young people. Through a public private partnership funded by the Innovative Medicines Initiative 2 between 2018 and 2025 involving 10 large originator pharmaceutical companies and 33 academic and third sector organizations, the conect4children (c4c) network has developed high-quality trial support services to promote consistent delivery in pediatric trials in over 220 sites across 21 countries, addressing gaps in communication, site identification, feasibility, and trial support. This paper explores the development and implementation of these services, using the Technology Readiness Levels (TRLs) and Service Readiness Levels (SRLs) frameworks to measure service progression and operational maturity. The initiative successfully streamlined targeted aspects of trial support. Over 6 years the multinational coordination of pediatric trials moved from SRL1 to SRL8 and services have been deployed in a sustainable non-profit organization. Challenges encountered include variability in site readiness for clinical trials and processes. Differences between companies in methodologies for collecting data about trial setup prevented clear understanding of the benefits of the c4c approach. Sustainability of long-term infrastructure beyond IMI2 funding will be managed by a new, independent, non-profit organization, conect4children Stichting based on scale up of services provided to industry and academia. The findings provide generalizable insights and lessons applicable to other research networks seeking to build or improve similar infrastructures.